Pemanfaatan Media Sosial Facebook “Buletin Sikka” Sebagai Media Publikasi Kegiatan Pemerintahan (Studi Deskriptif Pada Bidang Protokol dan Komunikasi Pimpinan) - TB Inan Malywanni Woga; Intan Mustafa; Markus Kristian Retu (Jurnal Cakrawala Informasi, 2024)
This research aims to analyze the use of Facebook social media, especially the "Sikka Bulletin" page as a means of publishing government activities carried out by the Protocol and Communication Section of the Sikka Regency Leadership. In the digital era, social media has become an important means of disseminating information quickly and widely to the public. This research uses qualitative methods with a descriptive approach, as well as data collection techniques through participatory, non-participatory observation, and interviews with Facebook users and documentation. The research results show that the "Sikka Bulletin" is effective in conveying information related to government activities to the public. However, there are several aspects that need to be improved, such as optimizing posting times, increasing interaction with the public, and presenting more complete information. The improvements made can increase the effectiveness of publications and strengthen communication between the government and the community. Apart from that, a more effective promotional strategy is needed to expand the reach of the content. Overall, the Sikka Bulletin has great potential to become a more transparent and interactive publication media, so that it can strengthen relationships and encourage community participation in various government activities.